2014
DOI: 10.1097/inf.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Pneumococcal Meningitis and Bacteremia in Latin America and the Caribbean

Abstract: Pneumococcal meningitis and bacteremia are important causes of morbidity and mortality in LAC children <5 years of age. This systematic review provided evidence about the burden of pneumococcal disease and the serotype distribution to assess the impact the pneumococcal vaccines and to assist decision makers in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
0
14
0
2
Order By: Relevance
“…Early treatment of bacterial meningitis can prevent serious complications such as hearing loss, memory difficulty, learning disabilities, brain damage, seizures and death (1)(2)(3). Meningitis can be life-threatening and the condition is classified as a medical emergency.…”
Section: Introductionmentioning
confidence: 99%
“…Early treatment of bacterial meningitis can prevent serious complications such as hearing loss, memory difficulty, learning disabilities, brain damage, seizures and death (1)(2)(3). Meningitis can be life-threatening and the condition is classified as a medical emergency.…”
Section: Introductionmentioning
confidence: 99%
“…En contraste con la meningitis en la edad preescolar, los más frecuentes son S. pneumoniae y N. meningitidis y en menor medida el H. influenzae, por el impacto del programa ampliado de inmunización (27,28) . Adicional al cultivo de LCR, el hemocultivo se realizó en la mayoría de la población, lo cual permitió identificar con mayor probabilidad al microorganismo en su fase de diseminación hematógena previa a la invasión meníngea; como se reporta en otros estudios como el de Ciapponi et al, existe un alto porcentaje de bacteriemia en niños con MB especialmente menores de 5 años (29,30) .…”
Section: Discussionunclassified
“…The next important observation of our chart review is the proportionately higher death rates in diarrheal children under five years of age with Streptococcal bacteremia compared to those without Streptococcal bacteremia; although, this is statistically insignificant. However, a number of previous studies had found the association of higher case-fatality rates with Streptococcal bacteremia [ 38 , 39 ]. The failure of attaining the significant difference in deaths in our study might be due to selection of sick controls as they all had diarrhea and/or other co-morbidities such as edematous malnutrition and severe sepsis.…”
Section: Discussionmentioning
confidence: 99%